Badanie tlenowego rozkładu substancji organicznych w stabilizowanych osadach ściekowych = The study on aerobic decomposition of organic material in the stabilized sewage sludges - Kazimierczak, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sewage sludgs originates in the process of wastewater treatment and it is a waste, which contains organic master. Organic matter has an ability to putrefaction. Aerobic digestion is one of the proces of stabilization of his sludge. In this paper carried out an investigation on loss of organic master during aerobic digestion. The order of reaction and constatnt of chemical reaction rate was designated.
Keywords: rozkład substancji organicznej w osadach ściekowych; tlenowa stabilizacjaosadów ściekowych; aerobic digestion of sewage sludge; loss of organic matter